HARTA WARIS PADA ANAK ANGKAT MENURUT KOMPILASI HUKUM ISLAM DI PENGADILAN AGAMA SAMARINDA - Gunawan, Ariya (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTInheritance status for foster child according to islamic law compension in a religious court Samarinda, under the guidance of Bapak Dr. H. Abdul Rokhim, S.H.,M.Hum as a mentor lecturer I dan Ibu Gusti Heliana Safitri, S.H.,M.H. as a mentor lecturer II.The purpose of the study is to know how to position adopted child right according to the compilation of islamic law and how to settle the birthright of the adopted child according to the compilation of islamic law.The type of research in this study uses normative ad sosiological juridical research methods.The result showed that the birthright position of the adopted child according to the compilation of islamic law was as a legitimate child based on a court ruling by not deciding the customer or the blood with his biological parents. So the position of the adopted child is thus the position of the child who will be the successor and subsequent heir of his adoptive parents so that the right of a adopted child who also act as a subject of law even in the inheritance law of the adopted child islam is not entitle to a will but in the compilation of islamic law the adopted child is entitle to the so-called wills mandatory according to the law that sets the limit as much as one –third of their adoptiv parents ‘ estate and settlement of wills manatory are adopted children must also have an authentic property or court determination because if the heir party does not want to give the right one-third of the child ‘s inheritance will be able to submit the claim to the religious court Samarinda.For the religious court expected to provide an explanation of the united states of islamic law enforcement of islamic law of islamic 209 verse and the law’s concealed wire and certainly of the prosecution is a matter of the law, and the following the police of the police are being endeavaged to the public of the public, or the police of the public’s place or the cooperation of the rules to keep it to justice to keep justice and the sense of responsibility.Keywords : Birthright, foster child, compilation of islamic law